Theoretical study of interaction process of cutter for milling working equipment of excavator with soil - I. S. Kuznetsov (Вестник СибАДИ, 2021)
Introduction. The pipeline transport of the Russian Federation makes up a significant share in the economy of our country. However, the service life of many pipelines at the moment is several decades. In this regard, the number of emergency situations is increasing. Moreover, the degree of their impact on infrastructure and the environment is increasing from year to year. It is important to solve the problem of timely repair of the pipeline system using modern and effective methods. The use of mechanization means can significantly reduce the time of repair work and their cost.Materials and methods. As a result of the research, a mathematical model of the interaction of the cutter of the milling working equipment of a hydraulic excavator with the excavated soil has been developed. It takes into account the physical and mechanical properties of the soil and the speed of penetration of the cutter at the point of contact with the soil.Results. The dependence is obtained, which allows determining the force of penetration of the cutter of the milling working equipment into the soil.Discussion and conclusions. It is recommended to use the results of the performed theoretical studies for calculating the design and operating parameters in the design and creation of milling working equipment.